Utilization of Nickel Slag Waste for Concrete Brick Production through Mixing Technology for Tambea Community Empowerment - La Ode Dzakir; Mansyur Mansyur; Septi Adnan; Al Tafakur La Ode; Minson Simatupang; Romy Suryaningrat Edwin; Irmawatti Paula Tamburaka (CV. Insight Publisher, 2026)
Processing nickel slag waste into concrete bricks for community empowerment in Tambea Village, Pomalaa District, Kolaka Regency, is an innovative solution that combines environmental, economic, and social aspects. Indonesia, as one of the world's largest nickel producers, produces large quantities of nickel slag, which often accumulates and causes environmental problems. The purpose of this community service is to reduce the impact of nickel slag waste by utilizing it as a raw material for concrete bricks and empowering the village community through training in production, marketing, and business management. The community training has shown positive results, with 80% of participants expressing interest in producing concrete bricks from nickel slag after understanding the mixing, molding, and curing processes. The use of nickel slag also reduces production costs by up to 20% compared to using sand. However, the biggest challenge is dependence on the limited supply of nickel slag from nickel processing, which requires collaboration with local industries to ensure a sustainable supply. Furthermore, further training and ongoing mentoring are needed to ensure the long-term sustainability of this business. Overall, this community service demonstrates that utilizing nickel slag as a raw material for concrete bricks is not only beneficial for the environment but can also improve the economic well-being of village communities.